The Effect Of Massed Practice And Distributed Practice Methods Practice Method In Terms Of Arm Muscle Strength Training On The Accuracy Of Passing Down The Ball - Zam-Zami, Zulfi Nizar; Himawanto, Wasis; Harmono, Setyo (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This research aims to determine: 1) the impact of Massed Practice and Distributed Practice training methods on enhancing the accuracy of volleyball underhand passes, 2) the difference in underhand passing accuracy between students with high and low arm muscle strength, and 3) the interaction effect of training methods and arm muscle strength on the accuracy of volleyball smashes. The study employs a quantitative approach with experimental techniques and data collection through tests. The population consists of male students from class IX at SMPN 1 Pucanglaban Tulungagung, with a sample size of 30 selected through purposive random sampling. Data analysis was conducted using t-tests and ANOVA tests. The results are as follows: 1) There is a significant difference in the impact of Massed Practice and Distributed Practice training methods on improving the accuracy of volleyball underhand passes. This is evidenced by the t-test results showing a significance value of 0.011, which is less than the 0.05 threshold, leading to the acceptance of the null hypothesis (Ha). 2) There is no significant difference in underhand passing accuracy between students with high and low arm muscle strength. The t-test results indicate a significance value of 0.336, which is greater than 0.05, leading to the rejection of the null hypothesis (Ha). 3) There is a significant interaction effect between training methods and arm muscle strength on the accuracy of volleyball smashes. The calculation results yield a significance value of 0.006, which is less than 0.05, indicating the acceptance of the null hypothesis (Ha).